2013
DOI: 10.1557/jmr.2013.160
|View full text |Cite
|
Sign up to set email alerts
|

Compressive strength of hollow microlattices: Experimental characterization, modeling, and optimal design

Abstract: Recent advances in multiscale manufacturing enable fabrication of hollow-truss based lattices with dimensional control spanning seven orders of magnitude in length scale (from ;50 nm to ;10 cm), thus enabling the exploitation of nano-scale strengthening mechanisms in a macroscale cellular material. This article develops mechanical models for the compressive strength of hollow microlattices and validates them with a selection of experimental measurements on nickel microlattices over a wide relative density rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 21 publications
4
58
0
Order By: Relevance
“…For example, it has been observed that buckling can have a significant impact on the strength of a lattice with the strength-density relation of ߪ ௬ ∝ ߩ̅ ଶ.ହ [47]. In polymer and hollow nanolattices, we observed failure initiation at or near the nodes in most samples, which suggests that the nodes govern the strength scaling, similar to what has been observed in microlattices [32]. All the beams in lattice architectures terminate at the nodes at a sharp angle, which creates significant stress concentrations in these locations during deformation.…”
Section: Strengthsupporting
confidence: 76%
See 1 more Smart Citation
“…For example, it has been observed that buckling can have a significant impact on the strength of a lattice with the strength-density relation of ߪ ௬ ∝ ߩ̅ ଶ.ହ [47]. In polymer and hollow nanolattices, we observed failure initiation at or near the nodes in most samples, which suggests that the nodes govern the strength scaling, similar to what has been observed in microlattices [32]. All the beams in lattice architectures terminate at the nodes at a sharp angle, which creates significant stress concentrations in these locations during deformation.…”
Section: Strengthsupporting
confidence: 76%
“…A large body of theoretical and experimental work has been dedicated to creating new lattice architectures and investigating their properties [1,15,18,19,23,[30][31][32][33][34]. Most analytical models for the mechanical behavior of both 2D and 3D lattices are derived using beam theory, and these models generally predict that strength and modulus follow a power law scaling with relative density as ‫ܧ‬ = ‫ܧܤ‬ ௦ ߩ̅ ,…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Hollow microlattices behave differently in that the failure mode switches from yielding to elastic buckling at a theoretical transition density of 0.24ρ s σ y /E s (for L/D = 10 and θ = 60 • ). 13 For nanocrystalline Ni-7%P, this transition occurs at a density of 0.023 g/cm 3 ( Table I), indicating that most of the tested nickel lattices were buckling-limited. The relative strength of the nickel microlattices scales with relative density with an exponent of 2.06 and a pre-exponential constant of 2.5.…”
Section: T T T T T T Tc C C C C C C C C C C C C C C C C C C C C C C Cmentioning
confidence: 95%
“…13 Comparing the strength scaling of microlattices formed from parylene polymer and nanocrystalline Ni-7%P (which behaves more like a brittle metallic glass than a ductile metal) demonstrates that cellular architecture has as much impact on the mechanical performance of microlattices as the constituent material properties. For the copper, gold, and silica microlattices, no conclusions about the trends of strength vs. density can be drawn from the limited experimental data, which fall close to the transition densities.…”
Section: T T T T T T Tc C C C C C C C C C C C C C C C C C C C C C C Cmentioning
confidence: 99%
“…Introducing architectural elements enables creating structures that are lightweight, because they use a fraction of monolithic material with the same dimensions, and simultaneously strong since the architecture provides a way to more efficiently carry load in a structure. The mechanical performance of such architected solids on the macroscale is a function of the deformation mechanism and relative density of the structure, as well as of the constituent material properties, and this has been studied for both materials with cellular solid cores as well as bulk cellular solids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Cellular solids can deform by either bending or stretching of the elements, which is dictated by the geometry of the lattice and its nodal connectivity, and this bending or stretching behavior defines the deformation mechanism of the cellular solid [1,2,5,17,18].…”
Section: Introductionmentioning
confidence: 99%